Free Notariatan Legal Services For The Community Are Not Able To Under The Law of Notary Office and Code Of Conduct and Its Application In Cilacap Regency - Putri Mayasari (Authentica, 2020)
Notarial Legal Services for free to people cannot afford is one of the notary obligations which regulated in the Statute and Notary Code of Ethics, even tough most people assume that people who use Notary services are usually those who are financially capable, so it is very rare to find anyone not able to ask for free notary services, but the rule still exists and until now there has been no further explanation about the limits and procedures for its application, so giving rise to different comprehension in each of the Notaries, likewise happen in Cilacap Regency. Need to know wheter the regulation has comply the purposive of the law and the application of the regulation in Cilacap Regency. Study with the legal research with the statute approach and conceptual approach then analyzed qualitatively. The government should be able to immediately make implementing regulations from these provisions, the organization should also be more aggressive in socializing. This rule is expected to be applied to the deed of establishment of business entities in accordance with government programs.Keywords: Free Notariatan Legal Services, Notaries